CUSTOMS POLICY, CUSTOMS BUSINESS, CUSTOMS REGULATION: TO PROBLEM OF CONCEPTION CORRELATIONS - A. D. Molokovich; K. N. Shabeka (Наука и техника)
Theoretical and methodological comprehension of customs regulation place and role in provision of trade and transport activity under conditions of world integration processes is considered in the paper.The essence of such economic categories as «customs policy», «customs regulation», «customs and tariff regulation», «customs business» is ascertained with the help of justified argumentation, clear conception approaches.